Generation Adequacy of Isolated Small Power System - Azubalis, M.; Slusnys, D.; Dragasius, E. (Elektronika ir Elektrotechnika, 2014)
Adequacy of the power system is described as an ability of power system to maintain safe operation in different operational modes. The technical properties of the generating unit and physical properties of the primary mover are evaluated in order to achieve adequacy conditions for small power systems. Operation regimes are specific for every source of electrical power. Adequacy requirements should be maintained in small power system during the all operating conditions. Meeting adequacy requirements always means reliable power supply. Isolated operation of the Baltic power system is investigated in this paper. Hourly power balances of the characteristic seasonal weeks of the year 2016 and 2020 are provided. DOI: http://dx.doi.org/10.5755/j01.eee.20.4.2533